Unraveling the hidden link between asthma and depression among University students in Bangladesh - Tafajjal Islam; Masom Mia; Md. Abdul Hannan Mondal; Mohammad Jahid Hasan; M. Tasdik Hasan; Md. Golam Hossain (PLoS ONE, 2025)
Background Asthma is a severe long-term respiratory and multidimensional disease. It affects a large proportion of people worldwide. Knowledge regarding asthma and its impact on depression among university students in Bangladesh is very limited. The objective of this study was to investigate asthma, as well as to explore the relationship between asthma and depressive symptoms among university students in Bangladesh. Methods This study employed a cross-sectional design. Data was collected from Rajshahi University, Bangladesh. A total of 400 university students were recruited for this study. A semi-structured questionnaire was utilized to gather information from the participants. The primary outcome variable was asthma, which was assessed with the question: “Are you suffering from asthma (diagnosed by a doctor within the past year)?” Depressive symptoms were measured using the nine-item Patient Health Questionnaire (PHQ-9). Factors influencing asthma and its association were examined using a binary logistic regression model. Results The study revealed that 53 (13.3%, 95% CI: 10.1% − 17.0%) of the students were suffering from asthma. Three significant predictors of asthma among university students were found: (i) having a family history of asthma (p < 0.01), (ii) being underweight (p < 0.01), and (iii) being born as a second or later child (p < 0.01). Findings also revealed that 48.8% of students exhibited symptoms of depression, with a significantly higher prevalence among female students compared to males (65.3% vs. 38.8%). Having asthma was found to be significantly associated with increased odds of depression (OR = 2.65, p < 0.002). Students with a history of asthma had 165% of more likelihood to depressive symptoms compared to their non-asthmatic peers suggesting a significant association between depressive symptoms and asthma in this population. Conclusion A considerable number of university students in Bangladesh suffer from asthma, with several modifiable factors such as depressive symptoms associated with the condition. The findings of this research will assist health professionals, policymakers, and university authorities in addressing the health challenges faced by students.